Wrinkling and collapse of mesh reinforced membrane inflated beam under bending. (November 2016) - Tao, Qiang; Wang, Changguo; Xue, Zhiming; Xie, Zhimin; Tan, Huifeng
Abstract: A novel concept of mesh reinforced membrane (MRM) is proposed in this paper. The tensile collapse mechanism of MRM is elucidated based on three obvious deformed stages. An improved Shell-Membrane model is used to predict the wrinkling and collapse of MRM inflated beam which is verified by a non-contact experiment based on the digital image correlation technique. Further the wrinkling details including the wrinkling evolution, pattern, shape, stress distribution are simulated to evaluate the functions of MRM for loading-carrying capacity of inflated beam. Pressure resistant performance of inflated beam was studied at last. The results revealed that MRM shows a great improvement on the collapse moment of inflated beam. MRM contributes to restrain wrinkling evolution by changing the transfer path of loadings which results from dispersing stress distribution and changing wrinkling pattern. The results show good references to the wrinkling control and the improvement of load-carrying capacity of inflated beam. Highlights: A novel concept of mesh reinforced membrane (MRM) is proposed; A modified SM model is proposed to predict wrinkling and collapse of MRM inflated beam; Collapse load is improved evidently due to mesh and interaction between mesh and membrane; MRM restrains wrinkling evolution obviously by changing stress transfer path; MRM showed a great improvement on the ultimate pressure and performed remarkable bulging effect.